BANKRUPTCY ANALYSIS OF NATIONAL AIRLINES COMPANIES IN REGIONAL ASIA AFTER COVID-19 PANDEMIC - Asaduddin Abdullah; Noer Azam Achsani; Suhendi (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2020)
The Corona Virus Disease (COVID-19) was declared a worldwide pandemic by the World Health Organization (WHO) on March 11, 2020. The main pandemic countermeasure with physical distancing and limitation to travel heavily damaged the airline industry around the world, which slumps the direct revenue to the company. Hence, the industry should utilize this tight cash flow and the volatility business due to high operating costs and the high cost of labor. This situation could be worsening to the various national carrier in Asia already performs poorly far before COVID-19. Therefore, this research will predict the bankruptcy of four national airline companies in regional Asia using a modified version of Altman Z Score and Zmijewski Model. This research will show the current and future condition of financial performance in each company. Those National Airlines, namely PT Garuda Indonesia Tbk. (IHSG: GIAA), Singapore Airlines Ltd. (SGX: CL6), Thai Airways International (BKK: THAI), and Eva Air (TPE:2618). This study's results indicate financial distress and possibly to be bankrupt for two national airlines company, especially in Garuda Indonesia and Thai Airways, compared to other selected national airlines. Thus, those financial distress companies should carefully allocate remaining assets, liquidate the unproductive entities, and perform a company reconstruction to avoid bankruptcy in the future. Keywords: covid-19, bankruptcy analysis, regional airlines industry, modified altman z-score, financial distress